(3QSGdI aj GdYbjOIs - (3CMeO Hf eMeOs
(3ChdgG (B:s
(3GdMeO ddg GdPj TQY dfG ef GdOjf eG hUi Hg GdeQSdjf GdJeS efj HYV ef Sdcg Gddg JYGdi Edi eSdc GdJabg aj GdOjf hLYdg ddYde ef GdWGdHjf GdQGZHjf Cf GLeY dge eSGFd VQhQGJ GdOjf aj QSGdI de jQ dgG efgG eKd s
(3BNQgG (B:s
(3PcQg Ydi GdbGQj aj TQM GdeTGcGJ fbdG Yf GdSjhWj aj cJGHg GdfbGjI hCf PcQJgG dc eLedI JJCed ajgG eaUdI ajeG QCjJ faSc efUaI Hg aGTcQ Gddg Ydi Pdc JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds